Distinct Influences of Land Cover and Land Management on Seasonal Climate. Issue 21 (10th November 2018) - Singh, Deepti; McDermid, Sonali P.; Cook, Benjamin I.; Puma, Michael J.; Nazarenko, Larissa; Kelley, Maxwell
Abstract: Anthropogenic land use and land cover change is primarily represented in climate model simulations through prescribed transitions from natural vegetation to cropland or pasture. However, recent studies have demonstrated that land management practices, especially irrigation, have distinct climate impacts. Here we disentangle the seasonal climate impacts of land cover change and irrigation across areas of high agricultural intensity using climate simulations with three different land surface scenarios: (1) natural vegetation cover/no irrigation, (2) year 2000 crop cover/no irrigation, and (3) year 2000 crop cover and irrigation rates. We find that irrigation substantially amplifies land cover‐induced climate impacts but has opposing effects across certain regions. Irrigation mostly causes surface cooling, which substantially amplifies land cover change‐induced cooling in most regions except over Central, West, and South Asia, where it reverses land cover change‐induced warming. Despite increases in net surface radiation in some regions, this cooling is associated with enhancement of latent relative to sensible heat fluxes by irrigation. Similarly, irrigation substantially enhances the wetting influence of land cover change over several regions including West Asia and the Mediterranean. The most notable contrasting impacts of these forcings on precipitation occur over South Asia, where irrigation offsets the wetting influence of land cover during the monsoon season. Differential changes in regional circulations and moist static energy induced by these forcings contribute to their precipitation impacts and are associated with differential changes in surface and tropospheric temperature gradients and moisture availability. These results emphasize the importance of including irrigation forcing to evaluate the combined impacts of land surface changes for attributing historical climatic changes and managing future impacts. Plain Language Summary: Several regions have experienced substantial agricultural expansion and intensification to meet the needs of our growing population. While the effects of land cover change associated with agriculture have been extensively studied and included as a standard forcing in simulations of historical and future climate, the influence of a common form of agricultural intensification—irrigation—is not fully understood. Despite mounting evidence of its importance on regional climate, irrigation is still not considered a standard climate forcing. To isolate the influence of irrigation from land cover changes, we conduct a suite of simulations with a state‐of‐the‐art global climate model. Our analysis of nine regions with extensive agriculture and heavy irrigation demonstrates that irrigation has comparable climatic impacts to land cover changes. Across most regions, irrigation amplifies land cover forced changes. However, over parts of Asia, where irrigation rates are highest, irrigation contrasts land cover forced changes and the combined climate response to land cover and irrigation are opposite to what would be expected with land cover changes alone. Our results highlight the importance of including land management decisions in climate simulations for a more accurate understanding of how human activities shape climate, particularly over these regions, and have implications for management of the effects of future climate change. Key Points: Climate impacts of irrigation and land cover change are comparable in magnitude but opposite in sign over some regions, especially Asia Contrasting or amplifying effects of irrigation relative to land cover change extend beyond the growing season and can vary by season Local and remote impacts are linked to changes in moisture flux, surface and upper‐level temperature gradients, and regional circulations